Information technology strategies how leading firms use IT to gain an advantage - Rapp, William V. (New York Oxford Oxford University Press, 2011)
The focus of this text is to educate the reader on the strategic principles fundamental to using information technology to gain market control. It provides case examples of how to use IT to enhance existing core competencies and strategies.
Electronic reproduction.
Keywords: Information technology -- Management; Business -- Data processing; Strategic planning; Information technology -- Management -- Case studies; Business -- Data processing -- Case studies; Strategic planning -- Case studies